2021
DOI: 10.1021/acscatal.0c04955
|View full text |Cite
|
Sign up to set email alerts
|

Shedding Light on CO Oxidation Surface Chemistry on Single Pt Catalyst Nanoparticles Inside a Nanofluidic Model Pore

Abstract: Investigating a catalyst under relevant application conditions is experimentally challenging and parameters like reaction conditions in terms of temperature, pressure, and reactant mixing ratios, as well as catalyst design, may significantly impact the obtained experimental results. For Pt catalysts widely used for the oxidation of carbon monoxide, there is keen debate on the oxidation state of the surface at high temperatures and at/above atmospheric pressure, as well as on the most active surface state under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
(144 reference statements)
1
5
0
Order By: Relevance
“…9 Furthermore, different isomers can have distinct reactivities where metastable isomers have the potential to be more reactive than the most abundant stable structure. 3,10−13 The importance of structures to reactivity has also been seen for single-nanoparticle catalysts, 14 indicating the importance of taking into account the full structural diversity when attempting to identify structure−property relationships. 15,16 Naturally, determining the exact structure on the atomistic level is difficult.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Furthermore, different isomers can have distinct reactivities where metastable isomers have the potential to be more reactive than the most abundant stable structure. 3,10−13 The importance of structures to reactivity has also been seen for single-nanoparticle catalysts, 14 indicating the importance of taking into account the full structural diversity when attempting to identify structure−property relationships. 15,16 Naturally, determining the exact structure on the atomistic level is difficult.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These sub-nanoclusters have also been shown to be highly fluxional, meaning that they can populate and interconvert between multiple isomers at catalytically relevant temperatures , and even dramatically change morphology within the ensemble as the partial pressure of reactants changes . Furthermore, different isomers can have distinct reactivities where metastable isomers have the potential to be more reactive than the most abundant stable structure. , The importance of structures to reactivity has also been seen for single-nanoparticle catalysts, indicating the importance of taking into account the full structural diversity when attempting to identify structure–property relationships. , Naturally, determining the exact structure on the atomistic level is difficult . Additionally, catalyst dynamics are an important part of the reaction coordinate; dynamic restructuring has been observed experimentally, and multiple DFT studies have supported the fact that restructuring of active sites is relevant for many catalytic reactions. Furthermore, Imaoka et al have explicitly shown the isomerization of a Pt 4 cluster in real time using HAADF-STEM, visualizing the exact kinds of structural change addressed in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…35 These measurements provided kinetic analysis of phase transition mechanism in single metallic NPs under working conditions. 36 The main restriction of the methods presented thus far is their limited ability to acquire chemical information at the nanoscale that will uncover the nature and distribution of reactants, intermediates, and products. 37−39 Nanoscale chemical information under working conditions is vital for determining the influence of different sites on the observed catalytic performances of heterogeneous and homogeneous (electro)catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of single-particle plasmonic nanospectroscopy and mass-spectrometry was utilized to correlate single-particle and ensemble-based reactivity . These measurements provided kinetic analysis of phase transition mechanism in single metallic NPs under working conditions …”
Section: Introductionmentioning
confidence: 99%
“…To contribute to the quest of experimental method development that enables efficient and quantitative scrutiny of catalytic reactions on single nanoparticles, we have recently introduced the concept of nanofluidic reactors and used them in combination with plasmonic imaging and spectroscopy, together with mass spectrometry in the gas phase and with fluorescence microscopy in the liquid phase, using both nanofabricated particles and individually trapped colloidal nanocrystals as the catalyst. , One of the key traits of this nanofluidic reactor platform is that it ensures identical reaction conditions for the individual particles during an experiment while isolating each of them in its own nanochannel. Thereby, it enables highly parallelized studies of tens of single nanoparticles in the same experiment, whereby it eliminates errors and uncertainties inherent to the subsequent experiments traditionally used.…”
Section: Introductionmentioning
confidence: 99%